2000
DOI: 10.1063/1.1290449
|View full text |Cite
|
Sign up to set email alerts
|

Electrical depth profile of p-type GaAs/Ga(As, N)/GaAs heterostructures determined by capacitance–voltage measurements

Abstract: Capacitance–voltage measurements on metal-semiconductor contacts are used to examine depth-resolved electrical characteristics of GaAs/Ga(As, N)/GaAs heterostructures. The experimental depth profiles of the carrier concentration are compared with calculations based on self-consistent solutions of the Poisson equation. As-grown Ga(As, N) layers are p type, and hole concentrations of about 3×1016 cm−3 are observed for undoped Ga(As, N) layers with a GaN mole fraction of 3% and thicknesses below 80 nm. This hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 28 publications
3
39
1
Order By: Relevance
“…Polyakov et al [14] and Jenn-Fang et al [15] had reported a similar defect which was attributed to interfacial defect. P. Krispin et al [16] also detect this trap in p-type GaAsN samples and point that to interfacial trap center.…”
Section: Figurementioning
confidence: 85%
“…Polyakov et al [14] and Jenn-Fang et al [15] had reported a similar defect which was attributed to interfacial defect. P. Krispin et al [16] also detect this trap in p-type GaAsN samples and point that to interfacial trap center.…”
Section: Figurementioning
confidence: 85%
“…It is generally known that while the undoped GaAs is usually n-type, a dilute GaNAs can be p-type or n-type, depending on the growth conditions and the type of elemental sources used in different growth techniques. The results presented in the literature indicate that as-grown, unintentionally doped GaNAs grown by MOVPE [13,14] or MBE [15] is usually p-type, however for example a CBE growth can result in the n-type GaNAs material [16]. It has been speculated that this ptype background doping is a result of unintentional carbon contaminations [1,17,18].…”
Section: Methodsmentioning
confidence: 99%
“…However, also the valence band changes a little, and it has been recently shown that GaAsN/GaAs material system has type-I band alignment. 6,7 Various defects are formed in the material during the growth, and post-growth annealing can be used to eliminate some of them. 8,9 Intrinsic point defects identified in the arsenide-nitrides so far are an As Ga antisite, 10,11 an N interstitial, [12][13][14] and a Ga vacancy.…”
mentioning
confidence: 99%